2020
DOI: 10.48550/arxiv.2006.11896
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On two weight estimates for iterated commutators

Abstract: In this paper we extend the bump conjecture and a particular case of the separated bump conjecture with logarithmic bumps to iterated commutators T m b . Our results are new even for the first order commutator T 1 b . A new bump type necessary condition for the two-weighted boundedness of T m b is obtained as well. We also provide some results related to a converse to Bloom's theorem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…This result was recently improved by Lerner et al [19], who provided a wider class of weights (µ, ν):…”
Section: Introduction and Main Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…This result was recently improved by Lerner et al [19], who provided a wider class of weights (µ, ν):…”
Section: Introduction and Main Resultsmentioning
confidence: 89%
“…In [13], Cruz-Uribe et al only proved this conjecture is true for Φ(t) = t p ′ [log(e + t)] p ′ −1+δ and Ψ(t) = t p [log(e + t)] p−1+δ for some δ > 0. This conjecture is still open, and we refer readers to see [16,19,20] for more recent works about it. Analogue to the case of singular integral operators, Pérez [25] gave the following sufficient condition:…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…then inequality (1.5) holds. Recently, Lerner, Ombrosi, and Riviera-Ríos [28] have developed the first techniques for the iterated commutators T m b . They showed that if b ∈ BMO, Ā ∈ B p ′ and B ∈ B p , and…”
Section: Introductionmentioning
confidence: 99%